Supply Chain Risk Mitigation Strategy Using SCOR with HOR Method at PT. Putra Jaya Nanas - Stevani Agatha Yudiantoro; Farida Pulansari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The high consumer demand for processed pineapple fruit drinks increases competitiveness, which requires companies to identify and analyze the risks that exist in each company's supply chain activities. One of the companies engaged in the production of pineapple juice drinks experiences high production demand and several other obstacles that affect the performance of the company that is hampered. This study aims to analyze the supply chain in pineapple juice beverage production activities to identify the risks that occur. The solution was carried out using the SCOR model with the House of Risk (HOR) method. Based on the results of risk identification using the HOR stage 1, 20 risk events were obtained, which were caused by 29 risk agents. Through the calculation of the ARP value, 11 causes of risk are presented, which are input to the next calculation, namely the HOR stage 2. In stage 2, 16 risk mitigation designs were obtained that were able to minimize the risk of occurrence. From the effectiveness value of risk mitigation obtained based on the total effectiveness value and the degree of difficulty, it is determined that the highest value to be the company's priority, is recruiting machine technicians (PA4) of 1361.25, and the lowest value is ensuring that the automatic filling machine always works optimally (PA16).